Advances in management accounting. - Malina, Mary A. (Advances in management accounting,, 2018)
'Advances in Management Accounting' (AIMA) is a publication of quality applied research in management accounting. The journal's purpose is to publish thought-provoking articles that advance knowledge in the management accounting discipline and are of interest to both academics and practitioners. As one of the premier management accounting research journals, AIMA is well-poised to meet the needs of management accounting scholars. Featured in Volume 30 are articles on: Risk management and internal control: A study of management accounting practice; Properties of performance measurement and management systems used dialogically between parent companies and foreign subsidiaries; CEO turnover and major business restructurings; The effect of informed outside directors on investment efficiency; Proactive strategic responses to corporate sustainability pressures: A sustainability control system framework; On the interplay between strategic performance and managerial accounting.